PET/CT in Head and Neck Cancer (PET/CT, 2018)
This pocket book is an up-to-date guide to the diagnostic imaging of head and neck cancers. The focus is particularly on FDG PET/CT, with coverage of the basic principles, clinical indications, typical and atypical appearances, normal variations and artifacts, advantages, limitations, and pitfalls. Consideration is also given to emerging roles for PET/CT in head and neck cancer, including radiotherapy planning and treatment response monitoring, and to radiotracers beyond FDG. In addition, succinct information is provided on clinical presentation, diagnosis, staging, pathology, management, and other diagnostic imaging techniques. A brief discourse on the practice of guideline adoption is included. The book is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging (compiled under the auspices of the British Nuclear Medicine Society) and will be an excellent asset for clinicians, nuclear medicine physicians, radiologists, radiographers, technologists, and nurses who work in the field of head and neck cancer. .